Infection of Powdery Mildew Reduces the Fitness of Grain Aphids (Sitobion avenae) Through Restricted Nutrition and Induced Defense Response in Wheat - Kang, Zhi-Wei; Liu, Fang-Hua; Tan, Xiao-Ling; Zhang, Zhan-Feng; Zhu, Jing-Yun; Tian, Hong-Gang; Liu, Tong-Xian (Frontiers in Plant Science, 2018)
In natural ecological systems, plants are often simultaneously attacked by both insects and pathogens, which can affect each other’s performance and the interactions can be extended to higher trophic levels, such as parasitoids. The English grain aphid (Sitobion avenae) and powdery mildew (Blumeria graminis f. sp. tritici) are two common antagonists that pose a serious threat to wheat production. Numerous studies have investigated the effect of a single factor (insect or pathogen) on wheat production. However, investigation on the interactions among insect pests, pathogens, and parasitoids within the wheat crop system are rare. Furthermore, the influence of the fungicide, propiconazole, has been found to imitate the natural ecosystem. Therefore, this study investigated the effects of B. graminis on the biological performance of grain aphids and the orientation behavior of its endoparasitic wasp Aphidius gifuensis in the wheat system. Our findings indicated that B. graminis infection suppressed the feeding behavior, adult and nymph weight, and fecundity and prolonged the developmental time of S. avenae. We found that wheat host plants had decreased proportions of essential amino acids and higher content of sucrose following aggravated B. graminis infection. The contents of Pro and Gln increased in the wheat plant tissues after B. graminis infection. In addition, B. graminis infection elicited immune responses in wheat: increase in the expression of defense genes, content of total phenolic compounds, and activity of three related antioxidant enzymes. Moreover, co-infection of B. graminis and S. avenae increased the attraction to A. gifuensis compare to that after infestation with aphids alone. In conclusion, our results indicated that B. graminis infection adversely affected the performance of S. avenae in wheat through restricted nutrition and induced defense response. Furthermore, the preference of parasitoids in such an interactive environment might provide an important basis for pest management control.